1985
DOI: 10.1016/0376-8716(85)90066-3
|View full text |Cite
|
Sign up to set email alerts
|

Nalbuphine

Abstract: Nalbuphine is a potent analgesic with a low side effect and dependence profile in animals and man. Nalbuphine is distinguished from other agonist/antagonist analgesics in having greater antagonist activity and fewer behavioral effects at analgesic doses than pentazocine, butorphanol or buprenorphine. At equi-analgesic doses, nalbuphine is quantitatively similar to nalorphine in regard to its large ratio of antagonist to analgetic activity. Clinical studies have confirmed this balance of strong antagonist to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
121
0
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(132 citation statements)
references
References 24 publications
4
121
0
4
Order By: Relevance
“…The duration of nalbuphine's an algesic action is 3 to 6 hours (Forbes et al 1984;Schmidt et al 1985). The plasma half-life of an analgesic dose of nalbuphine (10 to 20 mg) after intravenous adminis tration in healthy volunteers has been estimated at be tween 1.9 and 3.7 hours (Aitkenhead et al 1988); Jail Ion et al 1989;Lo et al 1987).…”
Section: Butorphanol and Nalbuphine Administrationmentioning
confidence: 99%
See 3 more Smart Citations
“…The duration of nalbuphine's an algesic action is 3 to 6 hours (Forbes et al 1984;Schmidt et al 1985). The plasma half-life of an analgesic dose of nalbuphine (10 to 20 mg) after intravenous adminis tration in healthy volunteers has been estimated at be tween 1.9 and 3.7 hours (Aitkenhead et al 1988); Jail Ion et al 1989;Lo et al 1987).…”
Section: Butorphanol and Nalbuphine Administrationmentioning
confidence: 99%
“…antagonist actions under some conditions. Nalbuphine and butorphanol each have K agonist activity (Jaffe and Martin 1990; Schmidt et al 1985), whereas buprenor phine has K antagonist activity (Jaffe and Martin 1990;…”
Section: Implications For Treatment Of Cocaine Abusementioning
confidence: 99%
See 2 more Smart Citations
“…The social, health and economic costs of substance dependence (SD) are high (Nutt et al 2010); yet the universal efficacy of currently available treatments is limited, and the mechanisms of action of such treatments are poorly understood (Sturgess et al 2011; Tiffany et al 2012). Naltrexone, an opioid receptor antagonist targeting particularly the mu‐opioid receptor (MOR) subtype (Verebey & Mule 1975; Schmidt et al 1985), has been shown in randomized controlled trials to be effective in alcohol dependence (AD) but may be more effective in some individuals or subgroups and not others (Streeton & Whelan 2001) (Anton 2008; Sturgess et al 2011). The current study aims to examine the effects of naltrexone on the neural network changes associated with SD, specifically in poly‐drug SD and AD.…”
Section: Introductionmentioning
confidence: 99%